Comment on Nejati et al. Spatiotemporal Patterns and Historical Overview of Aedes Mosquitoes in Iran: A Systematic Review. Trop. Med. Infect. Dis. 2026, 11, 131 - Tahereh Sadat Asgarian; Mohammad Mehdi Sedaghat (Tropical Medicine and Infectious Disease, 2026)
In this paper, we critically review the article entitled “Spatiotemporal Patterns and Historical Overview of Aedes Mosquitoes in Iran: A Systematic Review” published in Tropical Medicine and Infectious Disease (2026, 11, 131) [...]